MiR-378a-3p promotes differentiation and inhibits proliferation of myoblasts by targeting HDAC4 in skeletal muscle development. Issue 12 (1st December 2016) - Wei, Xuefeng; Li, Hui; Zhang, Bowen; Li, Caixia; Dong, Dong; Lan, Xianyong; Huang, Yongzhen; Bai, Yueyu; Lin, Fengpeng; Zhao, Xue; Chen, Hong
ABSTRACT: Muscle development, or myogenesis, is a highly regulated, complex process. A subset of microRNAs (miRNAs) have been identified as critical regulators of myogenesis. Recently, miR-378a was found to be involved in myogenesis, but the mechanism of how miR-378a regulates the proliferation and differentiation of myoblasts has not been determined. We found that miR-378a-3p expression in muscle was significantly higher than in other tissues, suggesting an important effect on muscle development. Overexpression of miR-378a-3p increased the expression of MyoD and MHC in C2C12 myoblasts both at the level of mRNA and protein, confirming that miR-378a-3p promoted muscle cell differentiation. The forced expression of miR-378a-3p promoted apoptosis of C2C12 cells as evidenced by CCK-8 assay and Annexin V-FITC/PI staining results. Through TargetScan, histone acetylation enzyme 4 (HDAC4) was identified as a potential target of miR-378a-3p. We confirmed targeting of HDAC4 by miR-378a-3p using a dual luciferase assay and western blotting. Our RNAi analysis results also showed that HDAC4 significantly promoted differentiation of C2C12 cells and inhibited cell survival through Bcl-2. Therefore, we conclude that miR-378a-3p regulates skeletal muscle growth and promotes the differentiation of myoblasts through the post-transcriptional down-regulation of HDAC4.